The Anatomy to Genomics (ATG) Start Genetics medical school initiative: incorporating exome sequencing data from cadavers used for Anatomy instruction into the first year curriculum - Glenn S. Gerhard; Qunyan Jin; Barbara V. Paynton; Steven N. Popoff (BMC, 2016)
Abstract Background The increasing use of next generation DNA sequencing in clinical medicine is exposing the need for more genetics education in physician training. We piloted an initiative to determine the feasibility of incorporating exome sequencing data generated from DNA obtained from cadavers used for teaching Anatomy into a first year medical student integrated block-style course. Methods We optimized the procedure to obtain DNA for exome sequencing by comparing the quality and quantity of DNA isolated from several tissues by two different extraction methods. DNA was sequenced using exome capture and analyzed using standard methods. Single nucleotide variants (SNVs), as well as small insertions/deletions, with potential functional impact were selected by faculty for student teams to independently investigate and prepare presentations on their findings. Results A total of seven cadaver DNAs were sequenced yielding high quality results. SNVs were identified that were associated, with known physical traits and disease susceptibility, as well as pharmacogenomic phenotypes. Students presented findings based on correlation with known clinical information about the cadavers' diseases and traits. Conclusion Exome sequencing of cadaver DNA is a useful tool to integrate Anatomy with Genetics and Biochemistry into a first year medical student core curriculum.